Die Vorstellungen der Schüler vom Unendlichen (mathematica didactica, 2002)
This contribution describes the students’ ideas of the term cardinality of a set and the development of these ideas during their school attendance. It is based on the results of the research we carried out in the years 1999 – 2001 at thirty elementary schools and grammar schools in the North Bohemian Region.